ROYALTI HAK CIPTA PADA KONSER MUSIK HUT BNI TAHUN 2022 BERDASARKAN PP NO 56 TAHUN 2021 TENTANG PENGELOLAAN ROYALTI HAK CIPTA LAGU DAN/ATAU MUSIK: The Copyright Royalties for the BNI Music Concert in 2022 are Based on Presidential Regulation No. 56 of 2021 Concerning the Management of Copyright Royalties for Songs and/or Music - Samhita, Ni Made Anjani Cinta; Nugrahani, Rr. Aline Gratika (AMICUS CURIAE, 2024)
This research aims to provide an overview of royalty payments for the BNI Anniversary music concert in 2022 based on Government Regulation No. 56 of 2021. The concert featured several bands and 15 musicians who performed both their own compositions and those of others, while the concert audience was not charged any fee (free of charge). The research method employed was normative research, utilizing secondary data supported by interviews. The findings indicate that the organizers of the BNI Anniversary Music Concert 2022 have a duty to make royalty payments to the National Collective Management Organization (LMKN). The royalty payment rates for music concerts are in accordance with the Decree of the Minister of Law and Human Rights of the Republic of Indonesia No. HKI.2.OT.03.01-02 of 2016, which states that free and paid music concerts have different rates. Therefore, the BNI Anniversary Concert 2022 is still obligated to fulfill its duty to pay royalties.